Urban ethics: Towards a research agenda on cities, ethics and normativity. (March 2020) - Dürr, Eveline; Ege, Moritz; Moser, Johannes; Neumann, Christoph K.; Winder, Gordon M.
Highlights : Introduces, defines and sets the scope for a new approach in urban studies: "urban ethics". Identifies a new conjuncture of ethics. Relates urban ethics to social creativity, urban governance, moral economies, and social and environmental justice.